Pengaruh pengencer air kelapa tua yang berbeda varietas terhadap kualitas semen cair Kambing Boer pada penyimpanan 3-50C - Aziz, Achmad Fadhli; Salim, Muhammad Ade; Isnaini, Nurul; Yekti, Aulia Puspita Anugra; Susilawati, Trinil (Faculty of Animal Science, Universitas Brawijaya, 2018)
Artificial Insemination using liquid semen is technology reproduction can improve goat productivity without liquid nitrogen. The Purpose of this research was to determine differences of old coconut water varieties of red (Cocos rubescens) and green (Cocos viridis) as diluent Boer goat semen, based on motility, viability and spermabnormalities during storage at 3-50C. The materials used for this research was Boer goat fresh semen as much as 3 heads were collected 2 times a week. Experimental Design. The treatment were devided into three Treatmen, there were: P0 (Tris+ 20% egg yolk); P1 (old coconut water varieties red + 20% egg yolk); P2 (old coconut water varieties green + 20% egg yolk). The data were analyzed by randomized block design, if the result are different or significantly different then continued to be tested with Duncan's multiple range test. The result showed that during storage until days 4, P0 has the best result on motility (40,5 + 1,1 %), viability (45,18+ 1,56 %), and abnormality (1,89+ 0,59 %). While on the diluent using old coconut water green variety better then red variety. On day of 2 P1 and P2 have motility (61 + 1,3%) and (51+ 7,5%); Viability (67,14+17,99%) and (55,37+10,66%), abnormality (1,23 + 1,02%) dan (1,70+ 0,99%).